2012
DOI: 10.1088/0004-637x/756/2/112
|View full text |Cite
|
Sign up to set email alerts
|

A COMPREHENSIVE ANALYSIS OFFERMIGAMMA-RAY BURST DATA. II.EpEVOLUTION PATTERNS AND IMPLICATIONS FOR THE OBSERVED SPECTRUM-LUMINOSITY RELATIONS

Abstract: We present a time-resolved spectral analysis of 51 long and 11 short bright gamma-ray bursts (GRBs) observed with the Fermi/Gamma-Ray Burst Monitor, paying special attention to E p evolution within each burst. Among eight single-pulse long GRBs, five show an evolution from hard to soft, while three show intensity tracking. The multi-pulse long GRBs have more complicated patterns. Statistically, the hard-to-soft evolution pulses tend to be more asymmetric than the intensity-tracking ones, with a steeper rising … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
145
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 77 publications
(109 reference statements)
24
145
0
2
Order By: Relevance
“…This is supported by a number of correlations in which E p,i is involved: its correlation with E iso (Amati et al 2002), its time-resolved analogue (Golenetskii et al 1983;Yonetoku et al 2004;Ghirlanda et al 2011;Lu et al 2012;Frontera et al 2012), with the collimationcorrected energy E γ (Ghirlanda et al 2004) for long GRBs, and both E iso and the energy released in the X-ray band, E X,iso , in the three-parameter correlation, which holds for both long and short GRBs (Bernardini et al 2012;Margutti et al 2013). Thus, investigating the connection between E p,i and temporal properties can provide clues on the physics of the prompt emission.…”
Section: Discussionmentioning
confidence: 94%
“…This is supported by a number of correlations in which E p,i is involved: its correlation with E iso (Amati et al 2002), its time-resolved analogue (Golenetskii et al 1983;Yonetoku et al 2004;Ghirlanda et al 2011;Lu et al 2012;Frontera et al 2012), with the collimationcorrected energy E γ (Ghirlanda et al 2004) for long GRBs, and both E iso and the energy released in the X-ray band, E X,iso , in the three-parameter correlation, which holds for both long and short GRBs (Bernardini et al 2012;Margutti et al 2013). Thus, investigating the connection between E p,i and temporal properties can provide clues on the physics of the prompt emission.…”
Section: Discussionmentioning
confidence: 94%
“…The observation of an E pi -E iso relation in time-resolved spectra (e.g. Ghirlanda et al 2010;Frontera et al 2012;Basak & Rao 2012;Lu et al 2012) may also provide insights into the origin of the E pi -E iso boundary. Finally, Since the E pi -E iso relation is not an intrinsic property of GRBs, it may be difficult to use it to standardize GRBs (Ghirlanda et al 2006;Mészáros & Gehrels 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In case of GRBs with multiple but separable pulses, it is frequently observed that the first pulse shows a HTS evolution, followed by a jump in the peak energy during the onset of a second pulse, and then again showing a HTS evolution in the falling part of that pulse (see e.g., Lu et al 2012). A very similar behaviour is seen for GRB 151006A, though the presence of a second pulse is not seen in the lightcurve.…”
Section: Evidence For a Second Hard Pulsementioning
confidence: 74%
“…Several studies conducted for GRBs with single/separable pulses show definite evolution of the spectral peak (E p ), either hard to soft (HTS) or intensity tracking (IT) (Liang & Kargatis 1996;Kaneko et al 2006;Lu et al 2012;Basak & Rao 2014). However, for GRBs with overlapping pulses, this picture is complicated which is probably affected by pulse overlap (e.g., Hakkila & Preece 2014).…”
Section: Introductionmentioning
confidence: 99%